Fatores de impacto na rotatividade dos funcionários no setor industrial do vestuário: estudo de caso no APL de confecção na região sudoeste do estado do Paraná - Tesser, Rosevete Marta Marcello (2016)
The transformations inherent in the political and economic changes interfere in the organizational environment and challenges the people management area when it comes to attracting and retaining staff. In order to identify which factors motivate impact on employee turnover in the industrial sector of garment in the Southwest of Parana, businesses and employees that make up the companies in this segment participated in the survey. The methodology used the exploratory and descriptive research to raise a survey of qualitative and quantitative approach. The data were collected between June to October 2015 in 41 garment industries in the sector of Paraná Southwest region. Data collection was conducted through a questionnaire administered to 207 employees who voluntarily requested his resignation and 211 questionnaires were applied in industries that registered shutdown of employees at this period. The Likert scale was the means of detecting the frequency of the views of employees and survey respondents companies. To provide greater consistency to the findings, the data were analyzed statistically, using cause and effect diagram and Pareto chart. Statistical analyzes were prepared with Minitab software, version 17. It was found that the factors that impact for the voluntary termination of the employee's southwestern Paraná clothing industry are factors related to personal reasons, city change and change for the non-industrial sector. The wage factor also had its relevance. Among the factors that impact for employee termination by the industry, the financial situation due to the current economic climate was the most led the industry to turn off people during the survey period, however as internal factors fulfillment of production targets and absenteeism leads the management area of human resources or companies the need to implement actions that can minimize these factors. Therefore, it is concluded that it is the factors related to the voluntary resignation of the employee or the factors related to termination by the company, both have consequence in the economic, financial or social aspect of firms and households operating in the clothing sector.